Efficiency and Rentability of Islamic Banks in Indonesia - Haryanto, Sugeng; Bachtiar, Yanuar; Khotami, Wildani (inovator, 2020)
This study aims to analyze the influence of macroeconomic factors, efficiency, risk, financing to deposit ratio and CAR on the rentability of Islamic banks. This research is a quantitative descriptive. The study period was conducted in 2010-2019, with quarterly data. The data source is secondary data. Data collection techniques are done by documentation. Data is taken from www.ojk.go.id and www.bi.go.id. The type of data used is quantitative data. The research variables are rentability, efficiency, financing risk, FDR, Capital Adequacy Ratio (CAR) and macroeconomic data in the form of GDP and inflation. Rentability is measured by Nett operating margin (NOM), bank efficiency is measured using BOPO and financing risk is measured by non-performing financing (NPF). The analysis technique used is multiple linear regression. The results showed that the GDP variable did not affect rentability. Efficiency, risk, and CAR affect rentability. FDR does not affect rentability.